2020
DOI: 10.5115/acb.19.135
|View full text |Cite
|
Sign up to set email alerts
|

Sex estimation using subpubic angle from reconstructed three-dimensional computed tomography pelvic model in a contemporary Malaysian population

Abstract: Research in forensic anthropology is recent in Malaysia due to limited access to documented skeletal collections. However, advanced imaging techniques provide virtual bone samples for use in morphometric studies to establish populationspecific standards by virtual anthropology. This study examined sexual dimorphism in the subpubic angle using a threedimensional computed tomography model of the pelvis, in a contemporary Malaysian population. The sample comprised multidetector computed tomography (MDCT) scans of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
1
8
2
Order By: Relevance
“…Though our study findings cannot be generalized for our population due to the smaller sample size, this widely accepted simple rule of 90° SPA for sex determination may not still be applicable in our population as mean SPA in the male in our study is way more than the cut-off value. 4,5,6,7,8,9 SPA in our study is comparable to the SPA in the study done by Akhlaghi et al (140.0° ± 14.3° in male and 101.0° ± 13.3° in female), but wider than the SPA in above mentioned other similar studies. 8 The differences may be due to the different ethnic groups studied.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Though our study findings cannot be generalized for our population due to the smaller sample size, this widely accepted simple rule of 90° SPA for sex determination may not still be applicable in our population as mean SPA in the male in our study is way more than the cut-off value. 4,5,6,7,8,9 SPA in our study is comparable to the SPA in the study done by Akhlaghi et al (140.0° ± 14.3° in male and 101.0° ± 13.3° in female), but wider than the SPA in above mentioned other similar studies. 8 The differences may be due to the different ethnic groups studied.…”
Section: Discussionsupporting
confidence: 88%
“…The subpubic angle in the female is morphologically different from the subpubic angle in males with a widely accepted cut-off value of 90° for the discrimination. 4 However, our study showed a mean SPA in male (104.72° ± 10.47°) more than 90°. Though our study findings cannot be generalized for our population due to the smaller sample size, this widely accepted simple rule of 90° SPA for sex determination may not still be applicable in our population as mean SPA in the male in our study is way more than the cut-off value.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Sex estimate using SPA is highly accurate. 3,4 The size of the birth canal is determined by the size of the SPA, which is a significant criterion in vaginal delivery. Determining the normal range of SPA in different populations would undoubtedly aid obstetrics in the prediction of obstructed labor and, hence, minimize maternal mortality by considering rational treatment plans.…”
Section: Introductionmentioning
confidence: 99%